Towards large and powerful radio frequency driven negative ion sources for fusion. (6th January 2017) - Heinemann, B; Fantz, U; Kraus, W; Schiesko, L; Wimmer, C; Wünderlich, D; Bonomo, F; Fröschle, M; Nocentini, R; Riedl, R
Abstract: The ITER neutral beam system will be equipped with radio-frequency (RF) negative ion sources, based on the IPP Garching prototype source design. Up to 100 kW at 1 MHz is coupled to the RF driver, out of which the plasma expands into the main source chamber. Compared to arc driven sources, RF sources are maintenance free and without evaporation of tungsten. The modularity of the driver concept permits to supply large source volumes. The prototype source (one driver) demonstrated operation in hydrogen and deuterium up to one hour with ITER relevant parameters. The ELISE test facility is operating with a source of half the ITER size (four drivers) in order to validate the modular source concept and to gain early operational experience at ITER relevant dimensions. A large variety of diagnostics allows improving the understanding of the relevant physics and its link to the source performance. Most of the negative ions are produced on a caesiated surface by conversion of hydrogen atoms. Cs conditioning and distribution have been optimized in order to achieve high ion currents which are stable in time. A magnetic filter field is needed to reduce the electron temperature and co-extracted electron current. The influence of different field topologies and strengths on the source performance, plasma and beam properties is being investigated. The results achieved in short pulse operation are close to or even exceed the ITER requirements with respect to the extracted ion currents. However, the extracted negative ion current for long pulse operation (up to 1 h) is limited by the increase of the co-extracted electron current, especially in deuterium operation.